2015
DOI: 10.4067/s0718-85602015000100004
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de Intervención Innovadora: Consejería de Enfermería en Salud Cardiovascular en Atención Primaria

Abstract: La prevención de enfermedades cardiovasculares es un reto para los sistemas de salud. Objetivo: Establecer el efecto de una intervención innovadora de Consejería de Enfermería Personalizada, Presencial y Telefónica, dirigida a: control de factores de riesgo cardiovascular (hipertensión, dislipidemia, sobrepeso), mejoramiento de calidad de vida relacionada con salud (CVRS), fortaleciendo la autoeficacia, el apoyo social y estructurando el fenómeno "vivir con expectativas de cambio" en personas usuarias del prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…With regard to geographic location, studies were found from 21 countries, predominantly from Brazil (n = 45, 52.95%) [9, and Mexico (n = 7, 8.04%). [57][58][59][60][61][62][63] They also highlighted countries such as Iran, [64][65][66][67] United States, [68][69][70] Spain, [71][72][73] United Kingdom, [74][75][76] Chile, [77][78][79] Canada, [80,81] Colombia, [82,83] New Zealand, [84,85] Turkey, [86] Taiwan, [87] Italy, [88] Norway, [89] Germany, [90] England, [91] Netherlands, [92] Australia, [93] Israel, [94] Costa Rica [95] and Kenya. [96] Regarding the year of publication, the studies ranged between 1999 and 2021 so that a greater number was observed in 2017 (n = 11, 12.94%) and 2018 (n = 8, 9.41%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to geographic location, studies were found from 21 countries, predominantly from Brazil (n = 45, 52.95%) [9, and Mexico (n = 7, 8.04%). [57][58][59][60][61][62][63] They also highlighted countries such as Iran, [64][65][66][67] United States, [68][69][70] Spain, [71][72][73] United Kingdom, [74][75][76] Chile, [77][78][79] Canada, [80,81] Colombia, [82,83] New Zealand, [84,85] Turkey, [86] Taiwan, [87] Italy, [88] Norway, [89] Germany, [90] England, [91] Netherlands, [92] Australia, [93] Israel, [94] Costa Rica [95] and Kenya. [96] Regarding the year of publication, the studies ranged between 1999 and 2021 so that a greater number was observed in 2017 (n = 11, 12.94%) and 2018 (n = 8, 9.41%).…”
Section: Resultsmentioning
confidence: 99%
“…[97,98] Nurses act in the development of individual and group educational interventions that promote knowledge and competency construction and acquisition by patients, consequently, such nursing interventions encourage individuals' co-responsibility and self-efficacy in their self-care process, favoring compliance with healthy behaviors, achievement of improvements in biopsychosocial well-being and control of biochemical and anthropometric indicators. [41,53,66,77,79,89,92] Care aimed at promoting compliance with drug treatment also stood out in the catalysing change domain. It is known that compliance with pharmacological therapy, in association with non-pharmacological measures, it is crucial in controlling glycemic, blood pressure and lipid levels and, therefore, in preventing complications linked to these indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados positivos que presentaron las intervenciones realizadas, dirigidas e implementadas por las enfermeras/os en la disminución de los parámetros bioquímicos y en las medidas antropométricas fueron una estrategia efectiva para el control de los factores de RCV y el mejoramiento de las ECV (21) . En un estudio con 160 participantes se realizaron entrevistas individuales con valoración antropométrica, revisión de historias clínicas y tres sesiones grupales con teoría, práctica y contenido de estas enfermedades, así como recomendaciones dietéticas, dieta mediterránea y ejercicio, refirieron que las intervenciones de estilo de vida fueron necesarias y efectivas en la modificación del estilo de vida (22) .…”
Section: Discussionunclassified